2018
DOI: 10.1097/tp.0000000000002099
|View full text |Cite
|
Sign up to set email alerts
|

Race, Risk, and Willingness of End-Stage Renal Disease Patients Without Hepatitis C Virus to Accept an HCV-Infected Kidney Transplant

Abstract: Most patients will consider an HCV-infected kidney in some situations. Future trials using HCV-infected kidneys may enhance enrollment by targeting older patients and prior transplant recipients, but centers should anticipate that black patients' acceptance of HCV-infected kidneys will be reduced compared with white patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 25 publications
3
39
1
Order By: Relevance
“…Early pilot studies suggest that this is clinically feasible and excellent sustained virologic responses can be achieved both for kidney as well as other solid‐organ transplants. In addition, it was reported that between 29% and 82% of the potential HCV− kidney transplant recipients on the waiting list might be willing to accept HCV+ kidneys under certain scenarios . In an analysis using contemporaneous cost data from Medicare (in US dollars), we now report that in addition to providing extra years of life for patients, this technique results in lower costs.…”
Section: Discussionmentioning
confidence: 82%
“…Early pilot studies suggest that this is clinically feasible and excellent sustained virologic responses can be achieved both for kidney as well as other solid‐organ transplants. In addition, it was reported that between 29% and 82% of the potential HCV− kidney transplant recipients on the waiting list might be willing to accept HCV+ kidneys under certain scenarios . In an analysis using contemporaneous cost data from Medicare (in US dollars), we now report that in addition to providing extra years of life for patients, this technique results in lower costs.…”
Section: Discussionmentioning
confidence: 82%
“…Transplant programs and candidates, willing to accept the long‐term uncertainties, could consider expanding the utilization of these organs as a potential strategy to increase the number of transplants and decrease costs . Furthermore, a survey revealed that 82% of transplant candidates would consider an HCV positive organ in some situations . Transplants from HCV viremic to uninfected recipients should be performed in the context of scientific institutional review board approved protocols as recommended by the American Society of Transplantation consensus conference on the use of hepatitis C viremic donors in solid organ transplantation …”
Section: Discussionmentioning
confidence: 99%
“…In addition, we assumed only HCV+ candidates had access to HCV‐infected organs. Should research protocols providing HCV‐infected organs to HCV− recipients gain wider acceptance, opening the pool of HCV‐infected donors to HCV− recipients, there would no longer be a wait‐time advantage in delaying therapy and treating pretransplant would drive care. Although we modeled elbasvir/grazoprevir as salvage therapy, treatment guidelines do not offer specific recommendations for treatment failure in patients with ESRD; inferences were consistent when we considered sofosbuvir/velpatasvir/voxilaprevir as a salvage regimen instead.…”
Section: Discussionmentioning
confidence: 99%